The Post‐9/11 "Terrorism" Discourse and Its Impact on Nonstate Actors: A Comparative Study of the LTTE and Hamas. Issue 2 (April 2014) - Toomey, Michael; Singleton, Benedict E.
<x xml:space="preserve">Abstract</x> In the aftermath of the 2001 World Trade Center bombings, the application of the label "terrorist" to one of the parties in a given conflict can serve to deny political legitimacy, and can make possible the use of extreme measures to deal with them. This article compares the fortunes of the Liberation Tigers of Tamil Eelam and Hamas. Through the use of an analysis of contemporary discourses relating to terrorism, it is argued that, in the post‐9/11 world, successfully ascribing a nonstate opponent as a terrorist permits the use of overwhelming force. The discourse thus becomes a powerful political technology in the hands of state actors, regardless of the justification for its use.